Análise da abordagem de educação ambiental nos livros de biologia - PNLD 2018 - Soares, Damaris Camata (2019)
The textbook is still one of the main resources used by teachers in the classroom. In this sense, the analysis of themes conveyed by these works reveals which conceptions and approaches are considered by authors, publishers, and also by the State, responsible for the National Textbook Program (Programa Nacional do Livro Didático - PNLD). Environmental Education was consolidated as public policy in Brazil and, although it is a diversified field of study, we now perceive that it has been homogenized in reformist discourses of maintenance and social conservation. Environmental Education becomes important, therefore, not only for the discussion about environmental conservation but also for the understanding and transformation of social reality. With the analysis of the Environmental Education theme in Biological textbooks of the 2018 PNLD, we intend to reflect on how these contents are evidenced. In this scenario, we performed descriptive bibliographical research, in which the data were analyzed with a proposal based on the content analysis (CA) of Bardin (2016). The analysis pointed out that the theme is unevenly distributed in the analyzed collections. According to the National Environmental Education Policy (Política Nacional de Educação Ambiental - PNEA), Environmental Education needs to be developed as an integrated, continuous and permanent educational practice. Thus, it is necessary to approach the theme then, in an equal way in the programmatic contents, a fact not observed in the analyzed collections. The analysis also showed that terms referring to Environmental Education are found in all collections, mostly present in the body of the text, which we consider a positive aspect since environmental discussion must occur throughout the development of the theme and not as something parallel and disconnected from the content. In addition, we find that most of the registration units are in the respective collections, in the volumes in which contents related to ecology are approached. With regard to the current studies on Environmental Education, we noticed that the textbooks did not advance much on this subject, giving it the unique and exclusive objective of raising awareness for environmental conservation. In relation to the categorical analysis, the analyzed collections show a conservationist and pragmatic tendency, privileging the transmission of knowledge of ecological systems, with the intention of raising awareness and sensitizing individuals towards a socially responsible behavior.